Tumit Akilis, dan lain-lain esei - Khalid Jaafar, 1955-; Institut Kajian Dasar Malaysia (Selangor : Institut Kajian Dasar, 2001)
Essays on Islam and sociopolitical conditions in Malaysia.
Cover title.
In Malay.
Keywords: Islam -- Malaysia; Malaysia -- Politics and government; Malaysia -- Social conditions